Evaluation of apical seal between single cone and cold lateral condensation techniques after post space preparation at different timing - Safura Anita Baharin,; Dayana Hazwani Ahmad,; Farah Nur Athirah Mohamad Anuar, (Universiti Kebangsaan Malaysia, 2013)
Obturation technique may have an effect on the apical seal following post space preparation. This study aimed to evaluate the apical seal of single cone and cold lateral condensation obturation techniques after post space preparation at two different timing. A total of 120 decoronated, single-rooted human premolars were divided into two groups (n=50) based on canal preparation and obturation techniques; group A - hand ProTaper/ single cone and group B - modified double-flared/ cold lateral condensation. Each group was then subdivided into two subgroups (n=25) (subgroup I- post space preparation immediately after obturation; subgroup II- post space preparation 7 days later). The remaining 20 teeth served as positive and negative controls. The external root surface was coated with nail varnish, submerged in 2% methylene-blue dye and incubated at 37°C for 72 h. Each tooth was later sectioned apico-coronally at 1 mm interval and evaluated using dissecting microscope. The results revealed that obturation techniques do not affect the apical seal (p>0.05). Immediate post preparation groups achieved significantly better seal for both obturation techniques when compared with the delayed groups at the level 3 mm and above from the apex (p<0.05). Immediate post space preparation provides better apical seal regardless of obturation techniques used.